FUNGSI DIKIA RAPANO DALAM MOANTA MARAPOLE PADA PESTA PERKAWINAN DI NAGARI UJUNG GADING KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Yoza Delvianita; Syeilendra Syeilendra; Tulus Handra Kadir (SENDRATASIK UNP, 2014)
Abstract The article was aimed at raveling the function of Dikia Rapano in Moanta Marapole during a wedding reception at Nagari Ujung Gading Lembah Melintang Kabupaten Pasaman Barat. The design of the research was qualitative using descriptive method. The data were obtained through library research, observation, interview and documentation. The data was analyzed by classifying and arranged them systematically. The research findings showed that the music instrument Dikia Rapano was used in Moanta Marapole during a wedding reception, that was when the groom wore the traditional wedding dress, led to the bride house in the wedding procession, and then both of the bride and the groom went around the neighborhood. The functions of Dikia Rapano were (1) as an entertainment (2) as a media for communication (3) as a physical respond and (4) as a media of certain ceremony.   Kata kunci: Fungsi, Musik, Dikia, Rapano